Competence Mapping of Elementary School Teachers in Classroom Action Research as a Preliminary Effort to Empower Research Capacity for Professional Teacher - Laeli, Sobrul; Adri, Helmia Tasti; Suherman, Irman; Balghis, Lilis Fauziah (Pusdikra Publishing, 2025)
Teachers hold a central and strategic role as the main agents of educational transformation and as practitioners responsible for improving the quality of learning through reflective inquiry. Classroom Action Research (CAR) serves as a scientific and systematic framework that enables teachers to identify classroom problems, implement evidence-based interventions, and evaluate their effectiveness. However, empirical evidence in Indonesia shows that many elementary school teachers still experience significant challenges in conducting CAR due to limited understanding of research methodologies, inadequate technical guidance, and low confidence in academic writing. This study aims to comprehensively map the competence of elementary school teachers in implementing CAR by examining four critical dimensions: conceptual understanding, action planning, implementation and data collection, and research reporting. Employing a quantitative descriptive approach, the study involved 20 elementary school teachers in Citerep, Bogor Regency, as participants. Data were collected using structured questionnaires and analyzed through descriptive statistical techniques. The findings revealed that teachers’ competence remains low across all assessed aspects, with only 12% demonstrating sound conceptual knowledge, 15% capable of effective planning and implementation, and merely 5% able to prepare structured research reports that align with academic conventions. These results reflect the absence of a sustained mentoring culture and the lack of systematic institutional support for teacher-led research practices. The study underscores the need for continuous professional development programs, collaborative mentoring with higher education institutions, and school-based research communities that empower teachers as reflective practitioners. Strengthening teachers’ CAR competence is crucial not only for enhancing their pedagogical professionalism but also for fostering a sustainable culture of research-based teaching and learning in Indonesian elementary schools.